Art therapy as a non-pharmacological intervention for older people: applications, challenges and challenges in the face of an ageing population - Marco, Patricia; Redolat, Rosa (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2026)
Recent demographic changes in the Spanish population suggest that older adults are a priority group for research into strategies aimed at promoting healthy aging and well-being. This paper outlines the characteristics and challenges associated with this life stage, and explores the potential benefits of various art therapy-based interventions. Furthermore, it emphasises the importance of brain healthcare and enriched environments in promoting healthy ageing and preventing cognitive decline and dementia. It also explores the relationship between art and health, proposing artistic approaches, particularly art therapy, could promote the physical, mental and emotional health, as well as socialisation, of older adults. This paper presents some examples of such applications. Finally, it reviews the published literature on art therapy-based interventions aimed at older people, focusing on Spanish publications. Based on this review, the potential benefits of art therapy (both in the field of prevention and intervention) are analyzed, and different processes associated with aging and neurodegenerative diseases are addressed. The study concludes by discussing the potential usefulness of various art-based interventions using responsive art and artistic activism, with the aim of challenging stereotypes and negative perceptions associated with ageism related to ageing.